A novel route of revascularization in basilar artery occlusion and review of the literature. (10th June 2015) - Morales, Alejandro; Parry, Phillip Vaughan; Jadhav, Ashutosh; Jovin, Tudor
Abstract : Ischemia of the basilar artery is one of the most devastating types of arterial occlusive disease. Despite treatment of basilar artery occlusions (BAO) with intravenous tissue plasminogen activator, antiplatelet agents, intra-arterial therapy or a combination, fatality rates remain high. Aggressive recanalization with mechanical thrombectomy is therefore often necessary to preserve life. When direct access to the basilar trunk is not possible, exploration of chronically occluded vessels through collaterals with angioplasty and stenting creates access for manual aspiration. We describe the first report of retrograde vertebral artery (VA) revascularization using thyrocervical collaterals for anterograde mechanical aspiration of a BAO followed by stenting of the chronically occluded VA origin. Our novel retrograde–anterograde approach resulted in resolution of the patient's clinical stroke syndrome.